Mucoepidermoid carcinoma: A rare case report - Alok, Abhijeet; Hasan, Kamal; Singh, Shivani; Jha, Abhinav (Indian Journal of Case Reports, 2019)
Minor salivary gland carcinomas are rarely reported. Mucoepidermoid carcinoma (MEC) is one of the most common salivary glandmalignancies. MEC accounts for 1% to 2% of major salivary gland neoplasms and 9% of minor gland tumors. It is most commonly seenin the parotid gland and usually appears as asymptomatic swelling. However, the palate is a frequent site when it occurs in the minorsalivary glands. Follow-up of the patient is very important as local recurrence rate with conservative treatment is high. Here we arereporting a low-grade mucoepidermoid carcinoma involving palatal region in a 25-years-old female patient. The patient presented witha fast-growing swelling, invading the underlying anatomical structures and was treated successfully through the antrostomy procedure.